TANTANGAN DALAM PEMBAHARUAN SISTEM PERADILAN MELALUI PERKEMBANGAN TEKNOLOGI: E-COURT DAN E-LITIGASI SEBAGAI SARANA MENUJU PERADILAN MODEREN DI INDONESIA - Ummi Maskanah (Jurnal Hukum Mimbar Justitia, 2023)
Futuristically people are reluctant to settle their cases through the Courts. Not It is not uncommon for sharp criticism to be raised that the judiciary is considered slow and long, very expensive and unresponsive to justice, formalistic and technical (rechnically), and less uptodate, so that it is less efficient and effective, making it difficult for the public to obtain justice through the courts. Obtaining justice through the courts. Technological developments are utilized by the Supreme Court as a solution and at the same time to implement the principle of simple, fast, and light cost. This research is descriptive analytical, normative juridical and empirical juridical approach, analyzed qualitatively. Qualitatively analyzed. The results of the study found that the Supreme Court of the Republic of Indonesia creates a court that fulfills the principles of simple, fast and light cost through a new innovation called Electronic through a new innovation called Electronic Court (E-Court) and E-Litigation, through Supreme Court Regulation No. 3/2018 Jo. Number 3 of 2018 Jo. Perma No. 1 of 2018 and through a Cooperation Agreement between the Supreme Court of the Republic of Indonesia, the Attorney General's Office of the Republic of Indonesia, and the Ministry of Law and Human Rights of the Republic of Indonesia. Human Rights of the Republic of Indonesia Number 402/DJU/HM.01.1/4/2020, Number KEP-17/E/Ejp/04/2020, Number PAS 08.HH.05.05.05.05. PAS-08.HH.05.05 of 2020, but in practice there are still many obstacles that need to be addressed. Facilities and infrastructure and immediately revise the procedural law, both the Law on Civil Procedure procedural laws both the Civil Procedure Law and the Criminal Procedure Law.Â Keywords : Judicial System Reform; Modern Court; Electronic Court.